EFEKTIVITAS TANAMAN SELEDRI (Apium graveolens L.) SEBAGAI TANAMAN REPELENSI POPULASI DAN SERANGAN Spodoptera litura F. PADA BUDIDAYA BAWANG MERAH (Allium ascalonicum L.) DI DESA PESANGGRAHAN - Nur Habibatur Rohmah; Trisnan Alif; Fita Fitriatul Wahidah (Jurnal Matematika dan Sains (JMS), 2023)
Spodoptera litura F. is a plant pest organism (OPT) on shallot plants that must be prevented so that shallots become productive. One way to prevent it is good and not to damage the environment is the use of tumangsari plants in the form of celery plants. The purpose of the study was to determine the effectiveness of celery (Apium Graveolens L.) as a pest population of Spodoptera Litura F. Repellent Plants in the Cultivation of Shallots (Allium Ascalonicum L.) in Pesanggrahan Village. This research is an experimental study using a randomized block design (RAK) pattern, one way ANOVA test data analysis technique with 5% significance and post hoc follow-up test with the smallest difference analysis. The results showed that celery plants were effective in suppressing Spodoptera litura F. pest attacks. The most effective treatment was 4 PTS treatment which could reduce Spodoptera litura F. population and zinc intensity of Spodoptera litura F., which were 1.66 and 0, respectively. 15%.